Phenol-water extracts of gram-positive Listeria monocytogenes and gram-negative Salmonella typhimurium. Comparison of biological activities - Hofman, J; Pospísil, M; Mára, M; Hríbalová, V (Folia microbiologica, 1985)
Using phenol--water extraction, a lipopeptidopolysaccharide complex (LPPS) was isolated from Listeria monocytogenes. Some biological and immunological properties of LPPS were compared with lipopolysaccharide isolated by the same procedure from Salmonella typhimurium. LPPS possesses low pyrogenicity, but the immunological activity is comparable with LPS: slightly lower adjuvant and polyclonal stimulating effect, almost equal mitogenic effect on mouse spleen cells and higher mitogenic effect on human peripheral blood cells. The results are discussed in connection with the chemical structure of both substances.
Keywords: Phenols; Mice, Inbred BALB C; Listeria monocytogenes; Lipopolysaccharides; Mice; fenol; Mitogens; fenoly; Bacterial Proteins; aktivace lymfocytů; zvířata; Macromolecular Substances; Lymphocyte Activation; horečka; Salmonella typhimurium; makromolekulární látky; lipopolysacharidy; myši inbrední BALB C; Phenol; Fever; myši; mitogeny; adjuvancia imunologická; Solubility; Adjuvants, Immunologic; bakteriální proteiny; rozpustnost; Animals